If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 36 + -6y Solving x = 36 + -6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = 36 + -6y
| 19x-22+7x=26x-22 | | log[8]32768=x | | 2x+7=2x+13 | | 3(2f-1)=6f+5 | | 8(4-s)+s=8+s | | 4x+10=80 | | 7(7-3r)=-r-11 | | 7(7-3r)=-r-121 | | -6m+7=7m+10 | | .125v=.25 | | 8x+1=0 | | -12-17=-89 | | 4y-5+y+51=8y+50-5y | | (2x^3y^4)5= | | .66x=-8 | | (y^4)2= | | (-2x^3y^2)(-3x^2z^2)(-5y^3z^3)= | | 4(2x+7)-6(4x-8)=12x+3(4x-9) | | (-x^2y^3z)(-x^3y^4)= | | (x^2y^4)(xy^7)= | | y-11y= | | 7(-6)+3(-5)= | | (7c^2)(-6c^4)= | | x^4-30x^2-125=0 | | slopey=4x+5 | | 91/4+(-43/3)= | | x^4-30x^2+115= | | s(x+t)=tx-m | | (y^2+4y)-(y^2+10y)= | | (x^2-3xy)-(-2x^2+xy)= | | 2c-8= | | 1-3x=10x-20 |